Expectant Mothers: Women’s Infertility and the Potential Identity of Biological Motherhood - Loftus, Jeni; Namaste, Paul (Qualitative Sociology Review, 2011)
Using the voices of 196 infertile women we analyze women’s infertility from the perspective of identity theory. Results illustrate how the potential identity of becoming a biological mother can have an extremely high level of salience, therefore women enact behaviors that attempt to make the potential identity of motherhood a reality. However, because a discrepancy exists between the potential and actual identities, these women experience harmful consequences until they either become pregnant or choose to stop infertility treatments. By understanding how these women create, interpret, and sustain the potential identity of being a biological mother while struggling to reject a possibly permanent infertile identity, this study offers new insights into both the social process of infertility and identity theory.